PENGARUH PROFESIONALISME PADA PERTIMBANGAN TINGKAT MATERIALITAS DENGAN ETIKA PROFESI DAN KREDIBILITAS KLIEN SEBAGAI PEMODERASI - Luh Putri Mas Mirayani; RR. Maria Yulia Dwi Rengganis (Badung: LPPM Universitas Triatma Mulya, 2021)
The aim purposes of this research to find empirical proof about the influence of profesionalism to materiality judegement and the influence of professional ethics and client credibility as moderating variables. Saturated sample method as the technique sampling. Data collection was done using questionnaires and dedicated to 86 auditors. Sample collections techniques use saturated samples. The number of respondents who filled out and returned the questionnaire in this study were 74 people. The analysis technique used in this study is Moderated Regression Analysis. The instruments have been examined for its validity and reliability. The model also has passed the classical assumptions of regression analysis. The result show that: (1) profesional ethics as moderating variable can’t moderate the inffluence of profesionalism to materiality judgement;and (2) credibility client as moderating variable can moderate the inffluence of profesionalism to materiality judgement.